The Influence of Transformational Leadership and Intellectual Capital on Organizational Agility with Organizational Learning as a Mediating Variable - Prasetyo, Aldryan Pniel; Nurhayati, Mafizatun; Mindarti, Ceacilia Sri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Objectives: This study aims to analyse the influence of Transformational Leadership and Intellectual Capital on Organizational Agility with Organizational Learning as a Mediating Variable. Methodology: The population of this study is soldiers in Puspenerbad 13 Squadron in Army Aviation Center headquartered in Kalimarau International Airport Area, Teluk Bayur, Berau, East Kalimantan which of 261 soldiers. The data analysis was conducted through Partial Least Square-Structural Equation Model (PLS-SEM). Finding: the result showed that Transformational leadership has no effect on organizational learning. Transformational leadership has no effect on organizational agility. Intellectual capital influences organizational learning. Intellectual capital affects organizational agility. Organizational learning affects organizational agility in 13-Assault Squadron. Organizational learning does not mediate the influence of transformational leadership on organizational agility and organizational learning mediates the influence of intellectual capital on organizational agility